2006
DOI: 10.1002/ijc.21644
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the matrix metalloproteinase‐1 gene promoter is associated with susceptibility and aggressiveness of head and neck cancer

Abstract: Matrix metalloproteinases (MMPs) play an important role in several steps of cancer development. A single guanine insertion polymorphism (2G) in the MMP1 promoter sequence at 21,607 creates an Ets binding site and thus results in enhancing transcriptional activity. This study aimed to evaluate the contribution of this 2G polymorphism on susceptibility and aggressiveness of HNSCC. A panel of HNSCC cell lines and peritumoral fibroblasts were examined for the MMP1 genotypes and expression levels. Genomic DNA was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Different genotyping methods were used in these studies, including the classical polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in 21 of 33 studies [17][21], [23], [25][30], [39], [41][48], PCR-allele specific refractory mutation system analysis (ARMS) in 2 studies [7], [40], TaqMan assay in 4 studies [19], [22], [34], [37], PCR-sequencing in 6 studies [24], [31], [33], [35]–[36], [38], and PCR – fluorescent fragment analysis in 2 studies [28], [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different genotyping methods were used in these studies, including the classical polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in 21 of 33 studies [17][21], [23], [25][30], [39], [41][48], PCR-allele specific refractory mutation system analysis (ARMS) in 2 studies [7], [40], TaqMan assay in 4 studies [19], [22], [34], [37], PCR-sequencing in 6 studies [24], [31], [33], [35]–[36], [38], and PCR – fluorescent fragment analysis in 2 studies [28], [32].…”
Section: Resultsmentioning
confidence: 99%
“…The significance of pooled ORs under the recessive model was also not influenced by omitting those four studies. In the present study, most genotype data were based on the time of diagnosis except for the studies [21][22] on the time of follow-up. Therefore, sensitivity analysis was performed by omitting the two studies.…”
Section: Resultsmentioning
confidence: 99%
“…The promoter polymorphism is responsible for lowering the transcription by disruption of an AP1-binding site [15], whereas the polymorphism A1082G has not been shown to have a phenotypic effect. The GG allele of the functional MMP1 G-1607GG polymorphism is associated with higher expression levels of MMP1 and with increased susceptibility to head and neck and lung cancer [16,17].…”
mentioning
confidence: 99%
“…Several chromosomal loci are deleted early during carcinogenic process. Le et al 16) reported that a stepwise allelic loss occurred involving 9p21, 3p, p53, RB1 or p16 and/or inherited genetic predisposition 25) or polymorphic alterations related with the activity of genes 26,27) could be responsible for aggressive tumor phenotype or secondary cancer development in younger patients. Those patients are likely to be cancer prone due to alterations of the TSGs or genetic predisposition for a long time.…”
Section: Resultsmentioning
confidence: 99%